Condylomatosis in pregnant - Assad, Tricia M.; Passos, Mauro R.L.; Bravo, Renato S.; Almeida Filho, Gutemberg L.; Pinheiro, Vandira M.S. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
With the clinicai detection of cases of condyloma in pregnant women in the Sector of Sexually Transmiued Diseases. a relevant lheme was discovered. This study explained the epidemiology of condyloma on pregnancy. once the women Human Papillomavirus infection presented itself as lhe most prevalent STD in the studies elaborated in pregnant women in our carc. For this reason. a retrospeclive study was initiated to examine the behaviorof HPV infection in pregnancy. The study was executed lhrough the analysis of potients' records of the firs1 clinicai visit during the period of January 1999 Lhrough July 2000 at the referred clinic. 1344 records were examined and 569 of lhe selected were female palients. Among these women. 12,5% were pregnant. Among those that were included in the selec1ion, a small amount didn't show clinicai signs of a STD (two paticnts) while 48 patients showed the papillomavirus infcction. The study focused on the analysis of the frequency of STD during pregnancy (specificallycondyloma), characterizing itsepidemiological profile and clinicai characteristics in this period of women's life. Toe results of 1he study show lhat these women have an average age of 19.5 years. most are single, but in exclusive relationships. Average education levei is slow. 85% ofthese women have some high School education a1 most. Along this line. 52,1% of the subject are uncmployed. most being in charge of farnily and domestic duties. The majority of the subjects (66.2%) live in households were the average income in less than 5 minimum salaries. Toe study showed that 59.1 % of Lhe subjects are first time pregnancies and 16.9% of lhe subjects had aborted or miscarried in the past. The most prevalent diagnoses were condyloma. which was present in 67.6% of the subjects, with thc majority of the cases in the second half of the pregnancy. lt was discovered that vaginal infection was shown to be contaminated in 45.8% of the condyloma case while association with alterations with cervical intraepithclial neoplasia (CIN) occurred in 10,4%. 85,4% of the subjects displayed externai genital lesions and 43.7% showed a multicentered characteristic. From 1hese results we can conclude that Lhe ectoscopic evaluation of the externai genitalia of an ante-natal care subject. by a trained team. can easily diagnose the specific characteristic of the H PV infection and can provide simple and inexpensivc lrcatment of one of the most common STD of this time.